Effect of N, P K, Ca and Mg Fertilizer Application on Peanuts in Tra Vinh Province, Vietnam - Nguyen, Tran Khanh Thi; Bui, Hieu Chi; Nguyen, Lang Thi (International Journal of Environment, Agriculture and Biotechnology, 2024)
This study was to evaluate the effects, determine the appropriate, fertilizers on peanut production. The experiment was installed in Tra Cu with two variety MD7, L14. Seven fertilizer treatments were designed. The treatments consisted of the application of T1:(Trichoderma sp + Bordeaux 1% + Probiotics 3M); T2: (organic fertilizer =10 ton/ha) ;T3:( Trichoderma sp + Bordeaux 1% + Probiotics 3M) + chemical fertilizers (35N-60P-60K + 150kg Ca + 40kg Mg ) + organic fertilizer 100%); T4: (Trichoderma sp + Bordeaux 1% + Probiotics 3M) + chemical fertilizers(35N-60P-60K + 150kg Ca + 40kg Mg ) + organic fertilizer 75% ;T5( Trichoderma sp + Bordeaux 1% + Probiotics 3M) + chemical fertilizers + organic fertilizer 50%) ;T6: chemical fertilizers (35N-60P-60K + 150kg Ca + 40kg Mg ) +(Trichoderma sp + Bordeaux 1% + Probiotics 3M) and T7 control and treatment of farmers: (120 N-60 P-60 K + 200 Ca kg/ha). The experimental design adopted consisted of randomized complete blocks with three replications. Results showed that the analysis of absorption N, P, K in the seeds, both varieties have statistical significance on the experiments. The treatment T5, with the highest N content (2.175) for MD7, and L14 variety (2.588). For P both varieties the highest N content at treatment T7. Only K with MD7 varieties the highest N content at treatment T7 and L14 in the treatment T4. The Ca and Mg content in the seed had the highest in treatment T5 with both two varities. For the leaf: +N content in the leaves in the treatment T2 was the highest N content (4.852) for MD7. For the L14 variety in the treatment T6 (4.989) (Trichoderma sp + Bordeaux 1% + CPVS 3M) for the highest N content, followed by the fertilization level in the treatment T3 (4,625) using probiotics (Trichoderma sp + Bordeaux 1% + CPVS 3M) + MKC chemical fertilizer + 100% organic fertilizer). P content, on MD7 varieties, at the treatment (T2) using only organic fertilizers and (T3) using biological products (Trichoderma sp + Bordeaux 1% + CPVS 3M) + MKC chemical fertilizers + 100% organic fertilizers for the highest P content (1.521; 1.365) respectively. K content, on the MD7 variety, at the treatment T2 and treatment T4, had the highest content (0.142; 0.102) respectively. For the L14 variety, the treatment T7 gave the highest K content (0.612). The leaves in the treatment T3 gave the highest Ca content. Mg content in the leaves depends on the age and genotypic location of the plant. On MD7 varieties, the highest Mg content in treatment T5 (1.140). For the L14 variety, at the level of treatment T3, use biological products (Trichoderma sp + Bordeaux 1% + CPVS 3M) + MKC chemical fertilizer + 100% organic fertilizer for the highest Mg content (0.712) and the lowest in T1 (0.012). It is essential to apply the correct dose and correct time for peanut at Tra Vinh.